1997
DOI: 10.1007/s004250050089
|View full text |Cite
|
Sign up to set email alerts
|

Light-stress-related changes in the properties of photosystem I

Abstract: Light-stress-related changes in photosystem I (PS I) were analyzed in photoautotrophic cultured cells of Marchantia polymorpha L. High light treatment (30 h; 1300 mol photons · m )2 · s )1 ) reduced the PS I-mediated electron-transport rate by more than 50% and the photochemical efficiency of photosystem II (PS II) by about 35%. In photoinhibited cells, 76% of the PS II centers remained closed in low light, which is in agreement with a preferential impairment of PS I. Our data indicate that excessive linear el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Furthermore, our results indicate that the susceptibility of PSI to photoinhibition is dependent upon the developmental history of the plant. We suggest that this may in part, explain the variability in the published literature regarding the susceptibility of PSI to photoinhibition [11–16, 38–41].…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Furthermore, our results indicate that the susceptibility of PSI to photoinhibition is dependent upon the developmental history of the plant. We suggest that this may in part, explain the variability in the published literature regarding the susceptibility of PSI to photoinhibition [11–16, 38–41].…”
Section: Resultsmentioning
confidence: 86%
“…In these reports, it was demonstrated that during light stress at low temperatures the maximum quantum yield of electron transport through PSI, the pool of photooxidizeable reaction center pigment of PSI (P700), and the efficiency of P700 oxidation were dramatically reduced [11–14]. Decreased levels of EPR‐detectable P700 + [10]and inhibition of PSI electron transport [15, 16]were also shown to occur in vivo under high light at ambient temperatures. Selective photoinactivation of PSI in isolated thylakoid membranes has been also reported at chilling temperatures and at 25°C in thylakoids isolated from either chilling sensitive or chilling tolerant plants [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is known that rapid photoinhibition of PSII protects PSI by reducing electron donation to P700 during high-light treatment at room temperature (25°C) or during moderate-light treatment at low temperature (4°C) (Sonoike 1995;Herrmann et al 1997;Tjus et al 1998), the interaction between PSI and PSII during recovery from chilling-induced photoinhibition was still unknown. In addition, Kudoh and Sonoike (2002) observed that during recovery process after chilling-light treatment in cucumber leaves, chlorophyll content continues to decrease and the amount of functional PSI per unit leaf area increases very slow.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, zeaxanthin is formed in the xanthophyll cycle and after prolonged light stress the pool size of xanthophyll cycle pigments is increased (SchaÈ fer et al 1994). Finally, we have demonstrated that light-stress treatment of M. polymorpha culture cells also results in characteristic changes in PSI organization (Herrmann et al 1997). Due to these pronounced high-light eects we decided to investigate the molecular organization of the photosynthetic apparatus in this species.…”
Section: Introductionmentioning
confidence: 63%